Consolidation in the DNS resolver market – how much, how fast, how dangerous?. Issue 1 (2nd January 2020) - Radu, Roxana; Hausding, Michael
ABSTRACT: Almost all online services use a domain name resolution function to translate names typed by the user into numbers that computers understand. This basic, recursive function, performed in milliseconds and invisible to the user, was integrated from the beginning into the operation of Internet Service Providers (ISPs). This started to change with the advent of new players – such as Google, Cloudflare, Oracle – operating public resolvers and rendering the market more dynamic in the last decade. As more technologies are developed to increase the privacy and security of the domain name system (DNS) protocol, large internet companies with global operations appear better equipped to integrate the latest requirements and offer their services free to users and ISPs, further consolidating their position in the market. This article provides a timely analysis of the emerging trends of consolidation in the recursive DNS services market, focusing on its evolution in the last decade and discussing empirical evidence for the shifts occurring from 2016 to mid-2019.